Spatial distribution of dengue fever and its association with entomological index in Kota Bharu for years 2014-2016 - Rahman, Nik Anisuddin Atiqi Wan Abdul (2017)
Background: Dengue fever is endemic in nearly 100 countries around the world. In Malaysia, there are some states that are endemic for dengue, including Kelantan. In 2014, Kelantan had the highest number of dengue fever cases during the last 15 years based on surveillance for dengue fever. Objective: The aim of this study was to describe the spatial temporal distribution of dengue fever cases in Kota Bharu and to determine the association between dengue fever cases and entomological index in Kota Bharu between 2014 -2016. Methodology: This analysis used the method of ecological studies conducted in January 2017 using secondary data from E-dengue surveillance system. The data obtained were secondary data from various formats including MS Excel and supported by a polygon shapefile ESRI. Multiple linear regression, according to years was used to assess the association between number of cases and the various entomological indices (Aedes index, Breateau index and Container index)Result: There were 16513 dengue cases have been notified to the E-dengue Surveillance system over a period of three years from 2014 to 2016 for the Kota Bharu district. Total case distribution showed four sub-districts, namely Kota Bharu, Kota, Panji and KubangKerian were endemic of dengue. In the multiple linear regression for year 2014, only the container index was significant, while for 2015 and 2016, only Aedes index was significant with regression coefficient 0.13 (95% CI 0.10 to 0.15), P = 0.001. While for 2015 and 2016, only Aedes index was significant with regression coefficient 32.37 (95% CI 24.43, 40.30), P = 0.001 and 54.90 (95% CI 48.29, 61.52), P = 0.001 respectively. Conclusion: Four main sub districts, namely sub district Kota Bharu, Kota, Panji and Kubang Kerian were endemic for Dengue Fever. Control and prevention should be intensified in this four endemic areas. Although the entomological indices were associated with the cases, its pathway would need further investigation.